The effects of algae and their products on heavy metal binding. - McKenzie, Colin N. (University of Ottawa (Canada), 1977)
Using ion-specific electrode and atomic absorption spectroscopy the heavy metal (HM) binding capacities of four Ottawa area natural water systems supporting algal blooms were examined, and the effects of HM ions and Anabaena 7120 on each other were studied. The HM binding capacities of the natural water systems studied during 1975 were much higher than those reported previously for Ottawa River water. The HM binding capacities of at least two systems had not decreased several months after the blooms disappeared. Ultrafiltration of the water did not decrease the HM binding capacities of the waters indicating that the HM binding substrate had a molecular weight of less than 500. Complete aching of the water samples removed the Hg 2+ binding capacity, indicating that organic carbon compounds formed the predominant HM binding substrate in the four water systems. Concentrations of 10-3M and 10-4M Cu(NO3)2 and Cd(NO3)2 completely inhibited growth of Anabaena 7120 in GO medium. Copper and cadmium concentrations below 10-4M produced an elongated lag phase compared to cultures with no HM ions present in the medium. When 10-5M nitrilotriacetic acid (NTA) was added to the medium with equal concentrations of Cu(NO3)2 or Cd(NO 3)2 the lag phase was further elongated. An elongated lag phase in Anabaena 7120 cultures was produced by 10-5M to 10-7M Pb(NO 3)2. Growth was not inhibited by 10-3, 10-4 or 10-8M Pb(NO3) 2 in GO medium. A heavy white precipitate formed in GO medium containing 10-3M and 10-4M Pb(NO3) 2. Atomic absorption analysis of Anabaena 7120 culture grown in GO medium containing 10-5 Cd(NO3) 2 had the same cadmium concentration associated with the cell fraction after the lag phase as at the beginning. In contrast, copper was almost completely released from the cells at the end of the lag phase.
Keywords: Environmental Sciences.